Economic dispatch of an islanded microgrid - Gowthami Thimmapathruni Venkata Satya; Chennapragada Venkata Krishna Bhanu (International Journal of Applied Power Engineering (IJAPE), 2022)
Microgrids are increasingly becoming popular to improve energy access and increase the resiliency of weakly connected rural networks. The economic operation of these microgrids with renewable energy resources is key for maximizing the benefits. The objective of this paper is to implement the economic dispatch of a microgrid using quadratic programming, considering the active and reactive power capability of the renewable energy resources. The open distribution system simulator (OpenDSS) is used for obtaining the load flow of the distribution network, and the converged solution is given as input to MATLAB for optimization. The simulation is carried out for one day with a variation of hourly load, solar PV radiation, and wind in both grid-connected and islanded modes under six different cases. The methodology is implemented on a modified IEEE-13 node test feeder distribution system. The simulation result shows that the microgrid with distributed generation (DG) capable of supplying both active and reactive power under islanded conditions is economical when compared to the grid-connected mode. The novelty of the work is that it considers the capability of distributed generation to supply both active and reactive power. That can make it fully autonomous as it can meet the hourly load requirement of the network under islanding mode as per IEEE Standard 1547.4.